Aluminum oxide nanowires as safe and effective adjuvants for next-generation vaccines. (January 2019) - Bilyy, Rostyslav; Paryzhak, Solomiya; Turcheniuk, Kostiantyn; Dumych, Tetiana; Barras, Alexandre; Boukherroub, Rabah; Wang, Fujia; Yushin, Gleb; Szunerits, Sabine
Graphical abstract: Abstract: Improving efficiency of an adjuvant, material that enhances the body's immune response to an antigen, has become vital for the development of safer, cheaper, and more effective next-generation vaccines. Commercial vaccines typically use aluminum salt-based adjuvant particles, most commonly aluminum oxyhydroxide (AlOOH) and aluminum hydroxide (Al(OH)3 ) based, often referred to as "alum". Despite their broad use, their adjuvant properties are rather moderate. This is even worse in the case of aluminum oxide (Al2 O3 )-based adjuvant. While being more robust and less cytotoxic, Al2 O3 is a significantly less effective adjuvant than above-mentioned Al compounds and is consequently not commonly used. Here, we report on the remarkably enhanced adjuvant properties of Al2 O3 when produced in the form of nanowires (NWs). Based on recent advances in understanding neutrophil activation by inert nanoscaffolds, we have created ultra-long Al2 O3 NWs with a high aspect ratio of ∼1000. These NWs showed strong humoral immune response with no damaging effect on the microvasculature. Since only the change of shape of Al adjuvants is responsible for the excellent adjuvant properties, our finding holds great promise for rapid implementation as safer and more effective adjuvant alternative for human vaccines. The mechanism behind human blood-derived neutrophil activation with Al2 O3 NWs was found to be sequestering of Al2 O3 NWs by neutrophils via formation of neutrophil extracellular traps (NETs).